Seismic Refraction Tomography and MASW Survey for Geotechnical Evaluation of soil for the Teaching Hospital Project at Mosul University - Al-Saigh, Nabil H.; JaddoaAl-Heety, Ahmed (Sulaimani Journal for Pure and Applied Sciences, 2014)
This study includes Seismic Refraction Tomography (SRT) and Multi-channel Analysis of Surface Waves (MASW) survey. 12 shallow refraction profiles and 2 profiles for MASW were conducted in teaching hospital project site in Mosul University to delineate some of shallow soil engineering characteristics for construction purpose. The linear arrays by using 12 geophones with 10 Hz frequency are used. Both of compressional (P) waves and MASW data were acquired and interpreted using seismic tomography method and MASW methods to create 1-D shear velocity model respectively. A number of engineering parameters such as Concentration Index, Material Index, Density Gradient and Stress Ratio are calculated. The seismic velocity values ,engineering, consolidation ,and strength parameter show that the site have three layers just as follows: the first one is the upper layer which corresponds to recent superficial deposits is characterized by an incompetent rock quality, the second one is the middle one that corresponded mostly to the river deposits composed especially of River terraces and clays is characterized by fairly competent rock quality While the third one is the lower layer is corresponded to the upper part of Fat’ha formation which is mostly composed of marl layers is good competent rock quality .Hence the 3rd layer is suggested for engineering and foundation purpose.
Keywords: Refraction Tomography; MASW; geotechnical investigation; engineering parameter